Manpower Planning in The Application of Teat Dipping To Control Sub Clinical Mastitis in The Small Dairy Farms - Anggraini, Raden Isma; Sudarnika, Etih; Pisestyani, Herwin; Wicaksono, Ardilasunu; Sudarwanto, Mirnawati (Jurnal Manajemen dan Agribisnis, 2020)
The application of teat dipping to control subclinical mastitis especially in small dairy farms is important; however, the application needs additional activity that has an impact on labor usage. This paper aimed to describe the labor usage to apply teat dipping for subclinical mastitis control in the small dairy farms. The convenience sampling techniques applied to select 34 farmers in Bogor as the respondents. Workload analysis and labor productivity were used in examining the application of dot dipping in various small dairy farms in Bogor City to control subclinical mastitis. This study was based on two types of experiments in small dairy farms in Bogor, West Java, namely teat dipping and without teat dipping. The findings show that the application of teat dipping had an impact on three things, namely an increase in labor usage and its workload, an increase in labor productivity and a decrease in the number of subclinical mastitis prevalence. This study concluded that labor was an important factor to control subclinical mastitis in small dairy farms. An increase in labor productivity had an impact on reducing the costs of mastitis treatment and finally increase farmer’s income. Keywords: mastitis, labor, small dairy farms, teat dipping, workload analysis